Guiding Inquiry toward Sustainability: The Role of POGIL in Enhancing Grade 10 Students’ Chemical Literacy in Green Chemistry - Muliaman, Agus; Dewi, Ucia Mahya (SAINTIS Publishing, 2025)
This study investigated the effect of the Process Oriented Guided Inquiry Learning (POGIL) model on Grade 10 students’ chemical literacy in Green Chemistry topics using a quantitative experimental approach with an intact group comparison design. Two pre-existing classes were assigned as an experimental group taught using POGIL and a control group taught using Direct Instruction, with posttest-only assessment. The sample consisted of 59 Grade 10 students selected through purposive sampling (30 experimental, 29 control). A PISA-style chemical literacy test measuring content, context, and competency dimensions was used as the research instrument. Data were analyzed using descriptive statistics, tests of normality and homogeneity, and an independent samples t-test at a significance level of 0.05. The results showed that students taught using POGIL achieved a higher mean chemical literacy score (81.1) than those taught using Direct Instruction (70.1), with the difference being statistically significant (p 0.05). These findings demonstrate that the POGIL model has a positive effect on students’ chemical literacy in Green Chemistry contexts and supports its application as a literacy- and sustainability-oriented instructional approach.